Respuesta :
Answer:
[tex] \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star[/tex]
Step-by-step explanation:
[tex]: \implies{ - 3(2x - 1) - 3x - 4 = 17}[/tex]
[tex]: \implies{ - 6x + 3 - 3x - 4 = 17}[/tex]
[tex]: \implies{ - 6x - 3x + 3 - 4 = 17}[/tex]
[tex]: \implies{ - 9x - 1 = 17}[/tex]
[tex]: \implies{ - 9x = 17 + 1}[/tex]
[tex]: \implies{ - 9x = 18}[/tex]
[tex]: \implies{ \displaystyle{x = \frac{18}{ - 9} }}[/tex]
[tex] \: \: \: \: \: \: \: \: \star{ \: \implies{ \red{x = - 2}}}[/tex]